PENINGKATAN PERILAKU PENCEGAHAN STROKE PADA LANSIA MELALUI PENGEMBANGAN MODEL PEMBERDAYAAN KELUARGA DAN LANSIA - Riasmini, Ni Made; Resnayati, Yeti; Silaswati, Shinta; Riyanto, Riyanto; Salmid, Amid (Universitas Pelita Harapan, 2025)
Introduction: The number of patients with hypertension is steadily increasing and poses a significant chronic health problem. Individuals with hypertension have an 87.5% risk of experiencing a stroke. The role of family as caregivers is crucial in elderly care, particularly in stroke prevention. The family empowerment model is an approach designed to enhance self-potential, enabling individuals to make informed decisions regarding their own health. This study aimed to examine the effect of a family empowerment model on stroke prevention behavior among the elderly with hypertension. Methods: This quasi-experimental study involved 132 families with hypertensive elderly, using multistage random sampling. A six-week intervention program consisting of education and skill-building activities was implemented. Stroke prevention behaviour was measured using the validated Elderly Stroke Prevention Behaviour Questionnaire (knowledge, attitude and behaviour). Data were analysed using paired and independent t-tests. Results: Significant improvements were observed in the intervention group following the implementation of the family empowerment model (p < 0.001). Knowledge scores improved from 6.61 (SD = 1.86) to 9.15 (SD = 0.88), attitude scores improved from 17.11 (SD = 2.30) to 25.79 (SD = 3.30), and behaviour scores improved from 7.18 (SD = 2.20) to 9.02 (SD = 0.97). Conclusion: The eight-week empowerment model effectively improved stroke prevention behaviour among the elderly with hypertension This model can be integrated into community-based programs to promote elderly self-care and reduce the risk of stroke. Recommendations: Empowering the elderly is essential to enhance self-efficacy and overall quality of life.